Status of HIV/Aids in Nigeria: communication issues, trends and challenges (2021)
Decades after HIV/AIDS appeared on global public health arena, it has remained a major public health issue that has social, political and cultural implications. Considering that there is no vaccine and cure for HIV/AIDS, globally countries (including Nigeria) have continued to deploy the tools of communication in providing its citizenry with key information about the disease and how and where to access available treatment opportunities This paper examined the current status of HIV/AIDS in Nigeria, communication issues, trends and the challenges. Although Nigerian government and relevant stakeholders have deployed mass media tools in the fight against HIV/AIDS, the prevalence in the country appears not to be abating. The paper identified some barriers to communication efforts that need to be addressed in order to contain the disease. The paper also argues that communication effort should not only be stepped up and the tempo maintained, but it should also target the most vulnerable groups in the society (the youths, men who have sex with men, those who inject drugs). Furthermore, the paper identified the potentials inherent in the social media that could be tapped into in reaching the youth population. The success of any communication efforts depends on the extent to which those who plan the communication campaigns identify and address the needs of the target population, with a view to effecting a behavioural change and achieving the desired health outcomes. It is important to note that education and communication remain the only viable weapons in the fight against HIV/AIDS pandemic.